2021
DOI: 10.3390/antiox10071122
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Physiochemical, and Biological Value of Muffins Enriched with Edible Insects Flour

Abstract: Edible insects are gaining attention as a novel food; however, studies with their use in food are still limited. This study aimed to determine the chemical composition, physical parameters, sensory acceptance, and biological properties of muffins enriched with different levels of cricket (Gryllodes sigillatus) and mealworm (Tenebrio molitor) flours. The approximate composition was analyzed, along with the physical and textural properties, color, and consumer acceptance. Moreover, the antioxidant properties, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
47
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 85 publications
15
47
1
3
Order By: Relevance
“…However, purchase intentions decrease drastically with increasing concentration of insect meal; 60% of the tasters would probably not be available to buy the crackers with 15% incorporation. Similar results were observed in the study by Zielińska et al [ 38 ], on the development of muffins enriched with T. molitor flour. The cracker containing a significant amount of insect flour was poorly appreciated by the consumer, especially in terms of taste and texture.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, purchase intentions decrease drastically with increasing concentration of insect meal; 60% of the tasters would probably not be available to buy the crackers with 15% incorporation. Similar results were observed in the study by Zielińska et al [ 38 ], on the development of muffins enriched with T. molitor flour. The cracker containing a significant amount of insect flour was poorly appreciated by the consumer, especially in terms of taste and texture.…”
Section: Resultssupporting
confidence: 92%
“…This was prominent during the realization of the dough, which was more difficult to mix and to handle. Similar results were observed, especially in the study of Zielińska et al [ 38 ] on muffin enrichment with T. molitor and cricket flour. This study showed that mealworm enrichment resulted in much softer crackers, but also in elasticity, resilience, cohesion, and chewiness of muffins, except for 6% and 10% flour incorporation (as in our study).…”
Section: Resultssupporting
confidence: 89%
“…In fact, in 2018, the European Food Safety Authority (EFSA) recognized insects as novel foods through the Regulation (EU) 2015/2283, and the Food Agriculture Organization (FAO) recommended including them in Western diets, aiming to cover the nutritional population gaps in proteins and fats [ 6 , 7 ]. Nowadays, insects are used in food manufacturing such as bread, pasta, muffins, extruded snacks, or even as meat analogs [ 7 , 8 , 9 , 10 ]. For around 2 billion people worldwide, insect species such as crickets, ants, grasshoppers, locusts, wasps, or bees are considered as food [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges will be to provide not only the right amount of food, but also an adequate supply of protein. The application of an unconventional source of protein—cricket powder (CP)—seems a promising approach to food for fortification with protein, vitamins, minerals such as Ca, Mg, K, Fe, Cu, Mn, and Zn, and dietary fiber [ 16 , 17 , 18 ]. The replacement of wheat flour with CP affects changes in the quality and digestibility of the product’s protein as well as the desirable essential amino acids profile [ 19 ].…”
Section: Introductionmentioning
confidence: 99%